Value Relevance of Financial Information: Empirical Evidence from Indonesia - Putri, Fara Ghassani; Panjaitan, Zulkarnain; Bangun, Bastanna Erlayas; Lestari, Henny Setyo; Leon, Farah Margaretha (International Journal Labs, 2023)
This research aims to analyze the factors that influence stock prices. The independent variables in this research are book value per share, dividends per share, earnings per share, operating cash flow per share, and return on assets, while the dependent variable is the stock price. The research sample used 45 (forty-five) consumer cyclical industry companies that were listed on the Indonesia Stock Exchange for the 2020-2022 period. The sampling technique used purposive sampling and the analytical method panel data regression. The results of the research explain that operating cash flow per share has a book value per share, dividends per share, and operating cash flow per share have a significant effect on stock prices, but earnings per share and return on assets have no effect on stock prices. The implication of the research that has been done is to provide direction for financial managers regarding the value relevance of financial information which can be seen from the book value per share, dividends per share, earnings per share, operating cash flow, and return on assets on stock prices. This research result is useful in the process of deciding on policies and assessing company performance. Meanwhile, the investors provide information that there is a strong relationship between financial information and stock prices.